FROM CITIZENS TO NATION: THE OTHER HISTORY. THE CUBAN NATION: DIFFERENCES AND SIMILARITIES WITH OTHERS NATIONAL FORMATIONS IN LATIN AMERICA IN THE XIX CENTURY. - Álvarez Pitaluga, Antonio Nestor (2018)
This article proposes an analysis about the Cuban nationality and nation process during the XIX century, in comparison with similar historical processes in Latin America. The paper gives some historical keys to understand the differences and similarities between the Cuban nationality historical process and other Latin American nationality processes in this century. At the same time, these keys allow to understand some historical realities of Cuba, nowadays.